(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У статті проаналізовано позиції давніх філософів щодо проблеми сім’ї, ролі жінки та чоловіка. Акцентується увага на духовно-моральному аспекті підготовки молоді до сімейного життя та важливості формування у майбутнього подружжя моральних якостей, наявність яких сприятиме створенню щасливої сім’ї. Ключові слова: сім’я, молодь, духовно-моральні якості, щастя, діти. The article deals with the opinions of ancient philosophers on the problem of family, roles of a woman and man in it. The attention is concentrated on the moral and spiritual side of the preparation of youth to family life, and also on the importance of formation of moral qualities, which will be helpful for a future couple in creating a happy family. Key words: family, youth, moral and spiritual qualities, happiness, children.